Comparison of measured and estimated crop evapotranspiration over Egypt - OMAR, MH; MEHANNA, AM (MAUSAM, 1986)
Mehanna (1976) estimated potential evapotranspiration (PE) for a number of meteorological stations in Egypt, using Penman’s method with adjustment of the constants of the radiation term and the aerodynamic term, such that they would agree with measurements of radiation in Egypt and with estimates by Omar ( 1971) of PE in a large field at Giza. Omar and Mehanna (1984) compared seasonal measurements of PE at Bahtim (near Cairo) using potential evapotranspirometers with Mehanna’s estimates of PE at Bahtim and with estimates by the methods given in the FAO Irrigation and Drainage Paper No.24 on "Crop Water Requirements” by Doorenbos and Pruitt (1977). The main features of the comparisons were that Mehanna, and three of thc FAO estimates (Blanev-Cridd1e, radiation, and pan evaporation) are within +- 10% of the measurements while the Penman estimate was 15% higher. Mehanna’s estimates of FE were used to calculite ET- crop (as -defined in 1he FAO paper) for 4 main crops in Egypt [cotton, maize, wheat and berseem (cover] at 9 meteorological stations, using crop coefficients given in the FAO paper. The estimated ET crop values- at meteorological stations enabled to calculate ET crop at a number of agricultural research stations. Estimates of ET crop were compared with measurements of crop evapotranspiration in conditions–similar-to those of ET crop, and also with measurements in all conditions including those of ET crop. The average ratio, for the four crops, of measured to estimated evapotranspiration was 0.95 and 0.80 respectively. Average ratios were also given corresponding to cases when the FAO Blaney.Criddle,’ radiation and Penman methods were used to estimate PE. It is concluded that the comparisons may probably confirm the reliability of applying Mehanna’s estimates of PE to the crop coefficients given in the FAO paper to estimate ET crop over Egypt.